Identification of lamprey variable lymphocyte receptors that target the brain vasculature - Jason M. Lajoie; Moriah E. Katt; Elizabeth A. Waters; Brantley R. Herrin; Eric V. Shusta (Scientific Reports, 2022)
Abstract The blood–brain barrier (BBB) represents a significant bottleneck for the delivery of therapeutics to the central nervous system. In recent years, the promise of coopting BBB receptor-mediated transport systems for brain drug delivery has increased in large part due to the discovery and engineering of BBB-targeting antibodies. Here we describe an innovative screening platform for identification of new BBB targeting molecules from a class of lamprey antigen recognition proteins known as variable lymphocyte receptors (VLRs). Lamprey were immunized with murine brain microvessel plasma membranes, and the resultant repertoire cloned into the yeast surface display system. The library was screened via a unique workflow that identified 16 VLR clones that target extracellular epitopes of in vivo-relevant BBB membrane proteins. Of these, three lead VLR candidates, VLR-Fc-11, VLR-Fc-30, and VLR-Fc-46 selectively target the brain vasculature and traffic within brain microvascular endothelial cells after intravenous administration in mice, with VLR-Fc-30 being confirmed as trafficking into the brain parenchyma. Epitope characterization indicates that the VLRs, in part, recognize sialylated glycostructures. These promising new targeting molecules have the potential for brain targeting and drug delivery with improved brain vascular specificity.